On-Farm Aquaculture Productivity and Economic Performance Data - Pant, Jharendu; Teoh, Shwu Jiau; Bhujel, Ram C (2024)
This dataset includes detailed records of on-farm trials such as fish growth rates, pond and water quality measurements, feeding schedules, and fish survival rates. Farmers' participatory grow-out trials following better management practices (BMPs) were conducted in two phases from 2015 to 2023 across ten farmers clusters in four municipalities in inlands. The trials in Phase 1 tested GIFT stocked at 3 fingerlings/m2 using green water in ponds and fed with locally made plant-based feed. In Phase 2, trials tested GIFT stocked at 5 fingerings/m2 with high quality imported pelleted feed supplemented with local feed and green water.